Higher interest to continue COVID-19 practice recommendations in non-pandemic times among German GPs with better crisis leadership skills (egePan study) - Benjamin Aretz; Yelda Krumpholtz; Simon Kugai; Nicola Amarell; Manuela Schmidt; Birgitta Weltermann (BMC, 2024)
Abstract Background The German College of General Practitioners and Family Physicians (DEGAM) issued a COVID-19 guideline with eleven recommendations to support primary care services during the pandemic. Their use in general practices beyond the pandemic can contribute to pandemic preparedness. This study analysed general practitioners' (GPs) interest in applying recommended organisational changes in non-pandemic times. Methods Data from the German egePan GP survey (n = 516 GPs) - a multi-level clustered randomised web-based survey - were analysed. GPs' interest in the future application of the eleven guideline recommendations was calculated. In addition, each recommendation was evaluated by the GPs using a Net-Promoter-Score (NPS range − 100 to 100). A linear regression model identified GP and practice characteristics associated with a higher interest in applying recommendations in non-pandemic times. Results 98.5% of the GPs indicated the intention to implement at least one guideline recommendation prospectively: disinfectant dispensers at the entrance (86%), optimised consultation scheduling to reduce waiting times (83%), and glass screens in the reception area (72%), which also received the highest NPS scores. In contrast, lower interest was observed for items such as insurance card readers handled by patients (48%), only selected staff treating infectious patients (44%), and video consultations for patients with infections (26%). A higher interest to implement recommendations in non-pandemic times was associated with a higher crisis leadership score (p < 0.001), using the Corona-Warn-App (p = 0.007), and being a female GP (p = 0.045). In addition, GPs from Western, Northern, and Southern, and those with a higher patient volume per three months, were more interested in future implementation. Conclusions Overall, GPs demonstrated the readiness to follow the DEGAM COVID-19 guideline outside pandemic periods, establishing them as key contributors to pandemic preparedness in Germany.